Azomesogens with tetra substituted benzene (مجلة ديالى للبحوث الانسانية, 2022)
In the present study , new series compounds : ( 4-n- Alkoxy -2,3,5,6 –tetra methyl phenyl – 4-n-alkoxy azo benzene .) homologues have been synthesized and characterized by IR ,HNMR , and elemental analysis , the mesomorphic character of the character of the compounds was studied by using differential scanning calorimeter (DSC) and polarizing microscope equipped with heating and cooling stage . To study the effect of the lateral groups on the thermal stabilities of the mesophase of the series, and the acting of broadening groups.